Effect of curcumin on the expression of Caspase‑3 and Bcl‑2 in the spleen of diabetic rats (Journal of Experimental and Clinical Anatomy, 2015)
Background: The spleen is the largest lymphoid organ, concerns with immunological reaction and filtration of blood. Diabetes mellitus is a primary disorder of carbohydrate metabolism that cause depletion of oxidant defense system. Curcumin has anti‑inflammatory, anti‑proliferative, anti‑apoptotic, anti‑bacterial, anti‑cancer and potent antioxidant activities. Aim of the Work: The purpose of this study was to clarify the effect of induced type I diabetes on the spleen of albino rat and whether these changes could be prevented by curcumin. Materials and Methods: Eighteen albino rats were divided randomly into three groups; control nondiabetic rats; untreated diabetic rats and curcumin‑treated diabetic rats. After 8 weeks of treatment, animals were sacrificed; spleen was dissected, processed and stained with hematoxylin and eosin and immunohistochemistry for activated Caspase-3 and Bcl-2. Results: Diabetes caused decrease in the body weight, degeneration of splenocytes, increased Caspase-3, and reduced Bcl-2 activity. Treatment with curcumin decreased the blood glucose level, prevented the loss of body weight and protected the spleen against diabetic induced structural changes. Conclusion: The current results suggested that consumption of curcumin protected the spleen against diabetic induced changes, reduced Caspase-3, and improved Bcl-2 expression. Thus, curcumin may attenuate the pathologic effects observed in the spleen of diabetic rats.